Elements of environmental science and engineering - Meenakshi, P (PHI Learning, 2012)
Designed as a text for all undergraduate students of engineering for their core course in Environmental Science and Engineering and for elective courses in environmental health engineering and pollution and control engineering for students of civil engineering, this comprehensive text, now in its Second Edition provides an in-depth analysis of the fundamental concepts. It also introduces the reader to different niche areas of environmental science and engineering. The book covers a wide array of topics, such as natural resources, disaster management, biodiversity, and various forms of pollution, viz. water pollution, air pollution, soil pollution, noise pollution, thermal pollution, and marine pollution, as well as environmental impact assessment and environmental protection. This edition introduces a new chapter on Environment and Human Health.